Dark Corners and the Limits of Ahmad Dehqan's War Front Fiction. Issue 1 (2nd January 2017) - Moosavi, Amir
Abstract: Since 2005, Iranian writer and veteran of the Iran-Iraq War, Ahmad Dehqan, has emerged as one of the most well-known writers of fiction based on that war. War fiction in Iran (as well as other forms of cultural production about the war) generally has adhered to the official narrative of 'Sacred Defense, ' which the Islamic Republic has promoted. The state also has been, and continues to be, the chief supporter of cultural production dealing with the war, particularly through institutions such as the Howzeh-ye Honari (Islamic Arts Center). Ahmad Dehqan is one such writer who is affiliated with the state. His fiction, however, particularly his novel Safar beh garā-ye devist va haftād darajeh (Journey to Heading 270 Degrees) and short story collection, Man qātel-e pesar-tān hastam (I Killed Your Son), not only fail to adhere to the norms of Sacred Defense fiction, but in many ways, attempt to undermine it. By focusing on two of Dehqan's short stories from the collection I Killed Your Son, this article argues that his fiction mines the recent past to challenge the authority of the Sacred Defense narrative by rewriting aspects of stories that took place during the war. In doing so, he reasserts the unsettled nature of the war narrative today in Iranian society and the continued interest and importance of the war.